Coupled thermal-electrical-optical analysis of a photovoltaic-blind integrated glazing façade. (15th October 2018) - Luo, Yongqiang; Zhang, Ling; Liu, Zhongbing; Su, Xiaosong; Lian, Jinbu; Luo, Yongwei
Highlights: PV-blind integrated glazing façade can balance building energy and daylighting performance. A thermal-electrical-optical model is theoretically built and experimentally validated. Thermal-electrical-optical performance of PV-blind glazing is investigated. The structural parameters of PV-blind are optimized. Abstract: PV-blind embedded double skin façade (PVB-DSF) is a promising façade system for building energy efficiency. This paper developed a coupled thermal-electrical-optical model for analyzing, evaluating and optimizing the system performance. The ray-tracing method, radiosity method and net radiation method are used for the optical model. The single diode R P -model and Lambert-W function are adopted in the electrical model. The airflow network and energy balance equations are coupled for system thermal model. A complex simulation algorithm is proposed for the thermal-electrical-optical model solution. A series of experiments were implemented for model verification. The comparisons between simulation and measurement data show a good agreement. Specifically, the relative mean square error (RMSE) for simulation result in optical model is 2.02 W/m 2 in sunny day and 5.21 W/m 2 in cloudy day; 2.24 V for output voltage and 1.47 W for output power; 0.67 °C, 0.41 °C and 2.17 °C for external, internal glass pane and PV-blind. On top of that, the model is used as a tool for understanding the system performance under different configurations and position of PV-blind, solar cell efficiency and airflow rate. PV-blind angle and width under different spacing settings are optimized for balancing system energy performance and indoor daylighting comfort level. This study offers a useful simulation tool and a deeper understanding of PVB-DSF, which is beneficial for the design, control, optimization and evaluation of this effective glazing façade and can contribute to building energy efficiency.